(untitled) (Journal Of Educational and Psychological Researches, 2017)
In recent years, the attention of the international community and intergovernmental and non-governmental organizations has grown into a new dimension of population displacement, called displacement within the country as a result of conflicts and the expansion of tacit groups, using sentences to describe such conflicts as "identity-based conflict", "ethnic conflict" "Sectarian conflict", in an attempt to determine the nature and characterization of those conflicts. In such conflict-stricken conditions, the value of a citizen - a person not directly involved in the conflict - is measured by the potential gains that that person has made to the conflicting parties, as civilians have been indirect victims of military operations, Favorite belligerent. When the population is not a direct target of the attacks, they are taken hostage, forcibly recruited, forced into forced labor, or moved to achieve a demographic, political, ethnic or sectarian balance. The problem of internally displaced persons has become a recognized phenomenon today and has become an important part of human rights and human rights organizations. The study is comprised of two theoretical and field aspects, and aims to shed light on the repercussions of the displacement crisis in the absence of security and social stability and on the principles of human rights and human development indicators, as well as the reasons that led to the sustainability of the displacement crisis in Iraq throughout history, And their implications for identity classification And to identify the obstacles of non-adaptation and integration with the customs and traditions of the community of displacement and their implications for their affiliations. The research employed a theoretical framework for interpreting the studied phenomenon. The field research was based on a random sample of 211 respondents from heads of displaced families in Arbil and Baghdad. It also used several scientific methods and statistical tools to collect data for analysis.